Optimization of headspace solid phase microextraction (HS-SPME) for the extraction of volatile organic compounds (VOCs) in MD2 pineapple / Syaidatul Faraha Zainuddin … [et al.] - Zainuddin, Syaidatul Faraha; Zakaria, Siti Raihan; Saim, Norashikin; Dol Hamid, Rossuriati; Osman, Rozita (Faculty of Applied Sciences, 2020)
Headspace solid phase microextraction (HS-SPME) was employed for the extraction of volatile organic compounds (VOCs) in MD2 pineapple (Ananas comosus L. var. comosus cv. MD2). Optimisation of HSSPME operating parameters was conducted using three-factor, three-level Box–Behnken response surface experimental design to evaluate the interactive effects of temperature (30 – 50 ºC), extraction time (10 – 30 min) and salting effect (1 – 3 g of salt addition) on the amount of selected VOCs. Determination of VOCs was done using gas chromatography with spectrometry detector (GC-MSD). Extraction temperature was found to be significant (p < 0.05) in increasing the amount of selected VOCs (ethyl acetate, methyl isobutyrate and butanoic acid methyl ester). Based on the maximum amount of these VOCs, the optimum operating extraction conditions for HS-SPME were set up at temperature of 30 °C, time of 29 min and salt addition of 1 g. The optimized HS-SPME conditions were employed for the extraction of VOCs from pineapple of different varieties.